O ceticismo e o naturalismo na filosofia de David Hume - Souza, Donizeti Aparecido Pugin (2014)
This work consists in an analysis of the relation between the skepticism and the naturalism presented in the philosophy of David Hume (1711-1776). It must be taken into account two important points of his epistemology: the self-definition as a skeptic, which serves as a counterpoint to the currents of philosophy that consider him only as a naturalist, and the awareness of the limits of this same skepticism, which should not be seen as a reliable resumption of the pyrrhonian skepticism, but as a mitigated or academic skepticism, as he himself notes it and proposes it. This way, it can be established a balance between these two points of convergence in his thought, understanding them as additional to the composition of the same human nature science. Our task is to establish a conciliation between the skepticism and naturalism in the philosophy of Hume, taking as a basis the mitigated skepticism defended by him in An Enquiry Concerning Human Understanding, and a unitary vision of his philosophical project from the human nature science, presented in the introduction to the Treatise of Human Nature.